2015
DOI: 10.3892/ijmm.2015.2443
|View full text |Cite
|
Sign up to set email alerts
|

Mori folium inhibits interleukin-1β-induced expression of matrix metalloproteinases and inflammatory mediators by suppressing the activation of NF-κB and p38 MAPK in SW1353 human chondrocytes

Abstract: The pro-inflammatory cytokine interleukin-1β (IL-1β) is known to play a crucial role in the pathogenesis of osteoarthritis (OA) by stimulating several mediators that contribute to cartilage degradation. Mori folium, the leaves of Morus alba L., has long been used in traditional medicine to treat diabetes, protect the liver, and lower blood pressure; however, the role of Mori folium in OA is not yet fully understood. Therefore, in the present study, we investigated whether Mori folium water extract (MF) inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 48 publications
4
36
0
Order By: Relevance
“…Furthermore, to investigate whether EESS can regulate upstream NF-κB signaling pathways, we examined the effects of EESS on MAPKs and PI3K/Akt pathways. Consistent with the results of previous studies [29,30,31], it was found that ERK, JNK, and p38 MAPK were activated in IL-1β treated chondrocytes, as evidenced by their phosphorylation. However, by pretreatment of EESS, only the activation of p38 MAPK was attenuated, and EESS did not affect the activation of ERK and JNK.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, to investigate whether EESS can regulate upstream NF-κB signaling pathways, we examined the effects of EESS on MAPKs and PI3K/Akt pathways. Consistent with the results of previous studies [29,30,31], it was found that ERK, JNK, and p38 MAPK were activated in IL-1β treated chondrocytes, as evidenced by their phosphorylation. However, by pretreatment of EESS, only the activation of p38 MAPK was attenuated, and EESS did not affect the activation of ERK and JNK.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, Mori folium possesses free radical-scavenging activities (Kim and Jang 2011, Iqbal et al 2012, Raman et al 2016, which may explain its antioxidant ability (Khan et al 2013, Raman et al 2016. Previous studies, including our recent data, indicated that the extracts and components of Mori folium have strong anti-inflammatory properties (Hong et al 2002, Shibata et al 2007, Chao et al 2009, Jeong et al 2016. Despite these encouraging studies, the effects and molecular mechanisms responsible for the anti-inflammatory and antioxidant potentials of Mori folium have remained elusive.…”
Section: Introductionmentioning
confidence: 97%
“…The dried leaves of M. alba were obtained from Bio-Port Korea, Inc. (Busan, Republic of Korea), and WEMF was prepared as previous described (Jeong et al 2016). WEMF was dissolved in a 100 mg/ml concentration with distilled water, and the stock solution was then diluted with culture medium to the desired concentration prior to use.…”
Section: Preparation and Fingerprinting Of Wemfmentioning
confidence: 99%
“…In our studies of the anti-inflammatory effect of 40% PeTP and in many other research papers, IL-1β has been shown to induce OA through the nuclear translocation of the NF-κB p65 sub-DOI: 10.1159/000496108 unit and MAPK phosphorylation [van den Berg, 2000;Goldring et al, 2011;Kim et al, 2011;Jeoun et al, 2016]. We thus confirmed the anticatabolic effects of 40% PeTP on the IL-1β-induced phosphorylation of MAPKs (ERK1/2, JNK, and p38) and the nuclear translocation of the NF-κB p65 subunit.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IL-1β-induced increase in expression is found in the synovial fluid and cartilage tissue of patients with OA [Dieppe et al, 1999;Zheng et al, 2017]. Thus, a reduction in the activity of cartilage-degrading enzymes and inflammatory mediators is expected to have beneficial effects, such as chondroprotection, against pathological conditions like OA [Jeoun et al, 2016]. In OA, cartilage destruction is closely related to chondrocyte dedifferentiation, which is modulated by multiple signaling pathways, including the nuclear factor (NF)-κB and mitogen-activated protein kinase (MAPK) pathways, such as ERK-1/2, JNK, and p38 [Kim et al, 2011;Goldring et al, 2011].…”
Section: Introductionmentioning
confidence: 99%